2016
DOI: 10.1038/srep29212
|View full text |Cite
|
Sign up to set email alerts
|

Arbitrarily tunable orbital angular momentum of photons

Abstract: Orbital angular momentum (OAM) of photons, as a new fundamental degree of freedom, has excited a great diversity of interest, because of a variety of emerging applications. Arbitrarily tunable OAM has gained much attention, but its creation remains still a tremendous challenge. We demonstrate the realization of well-controlled arbitrarily tunable OAM in both theory and experiment. We present the concept of general OAM, which extends the OAM carried by the scalar vortex field to the OAM carried by the azimuthal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 29 publications
(45 reference statements)
1
13
0
Order By: Relevance
“…Interestingly, it has been recently shown that light beams can carry fractional or non-integer OAM, i.e., photons can exhibit a half-integer angular momentum 3 4 5 6 7 8 9 10 . In this sense, conical refraction (CR) produced with optically biaxial crystals has been demonstrated to be an efficient method to generate half-integer OAM beams 11 12 13 14 15 .…”
mentioning
confidence: 99%
“…Interestingly, it has been recently shown that light beams can carry fractional or non-integer OAM, i.e., photons can exhibit a half-integer angular momentum 3 4 5 6 7 8 9 10 . In this sense, conical refraction (CR) produced with optically biaxial crystals has been demonstrated to be an efficient method to generate half-integer OAM beams 11 12 13 14 15 .…”
mentioning
confidence: 99%
“…For example, this feature leads to an increase in the modulation spectral efficiency, yielding higher bit rates for the same total bandwidth, as it can enable M-ary modulations in analogy to the well-established quadrature amplitude modulation scheme 17 . The generation of optical beams carrying FOAM is similar to the simultaneous generation of at least two copropagating OAM beams of different amplitudes, mainly relying on carefully aligned tabletop optical setups involving a noninteger spiral phase plate, a geometric-phase-designed J plate, metasurfaces, or a spatial light modulator [18][19][20][21][22][23][24] . The desired FOAM can be generated by delicately tuning the weighting between two distinguished OAM components.…”
Section: Introductionmentioning
confidence: 99%
“…Using an iris on a translation stage, adjustable perpendicular to the beam, we create a beam with restricted transverse coherence and show that the presence of an OAM state is dependent on the transverse coherence. The creation of fractional OAM states by such a technique is well known in the photon optical community, [14] but here we are interested in integer OAM states. After reviewing specifics of coherence and OAM states, we present our setup and main results.…”
Section: Introductionmentioning
confidence: 99%